2014
DOI: 10.7717/peerj.309
|View full text |Cite
|
Sign up to set email alerts
|

Using a pacifier to decrease sudden infant death syndrome: an emergency department educational intervention

Abstract: Background. Pacifier use decreases the risk of sudden infant death syndrome (SIDS). An emergency department (ED) visit may provide an opportunistic ‘teachable moment’ for parents.Objectives. To test the hypotheses (1) that caregivers were less familiar with the role of pacifiers in sudden infant death (SIDS) prevention than other recommendations, and (2) that an ED educational intervention would increase pacifier use in infants younger than six months, and (3) that otitis media would not occur more frequently … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, the skills, equipment and expertise for this are often not available when aiming to examine OM as part of a large‐scale, longitudinal, multidisciplinary population cohort, such as the present study. In such cases, parental‐report measures are often recommended and continue to be used to identify a broad presentation of OM that may include children with a wide range in severity of symptoms. The sensitivity of parental‐report OM has been estimated to be between 75 and 95%, with a specificity of 65–100%, with parents more likely to underestimate the number of episodes if the child had <6 episodes and overestimate episodes if the child had >6 episodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the skills, equipment and expertise for this are often not available when aiming to examine OM as part of a large‐scale, longitudinal, multidisciplinary population cohort, such as the present study. In such cases, parental‐report measures are often recommended and continue to be used to identify a broad presentation of OM that may include children with a wide range in severity of symptoms. The sensitivity of parental‐report OM has been estimated to be between 75 and 95%, with a specificity of 65–100%, with parents more likely to underestimate the number of episodes if the child had <6 episodes and overestimate episodes if the child had >6 episodes.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to distinguish between acute OM, OM with effusion (OME) or recurrent AOM, and there are different spectra of risks for these conditions [29]. Despite this limitation, recent studies used parental reporting to measure the prevalence of OM [7,33]. The Raine study (Western Australian Pregnancy Cohort) [6] used parental reporting backed up by otoscopic examination by a specialist nurse.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study found that pacifier use in the newborn nursery is a strong predictor of pacifier use later in infancy and that starting a pacifier before hospital discharge was associated with greater use and lower discontinuation in the following year. 29 In addition, a casecontrol study that explored the interaction of pacifier use and unsafe sleep conditions demonstrated a markedly attenuated SIDS risk in the presence of unsafe sleep conditions, including bed sharing, sleeping in the prone/side position, using pillows, and using soft bedding. 30 A recent British study also suggests that pacifier use is associated with a lower risk of SIDS in cosleepers.…”
Section: Discussionmentioning
confidence: 99%